A Study in Historical Fiction: John Ford's Perkin Warbeck and Mary Shelley's The Fortunes of Perkin Warbeck - Gasse, Paulette Rosanne (My University, 1981)
This thesis is a detailed study of two fictional works, John Ford's Perkin Warbeck and Mary Shelley's The Fortunes of Perkin Warbeck, which deal with the star; of the Royal Pretender Perkin Warbeck. It strives through these to show how historical fiction is written and how it relates to an author's own time and interests. It also glances at how historical fiction relates to posterity.
Keywords: English Language and Literature; English Language and Literature